PENINGKATAN PENGETAHUAN PETANI TENTANG DIVERSIFIKASI HASIL USAHA TANI BAWANG MERAH DI NAGARI KOTO GADANG GUGUAK JORONG BUKIT GOMPONG KABUPATEN SOLOK - Putri Meliza Sari (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2020)
One of the activities in agriculture that contributes is horticultural farming. Solok Regency is one area that has the potential to become one of the centers of onion production because it has been the area with the largest production and planting area of shallots in West Sumatra. This activity was followed by shallot farmers in Jorong Gompong, Solok Regency who will carry out a program of diversification of shallots to fried onions. This product diversification activity can create added value, and of course it will increase the income of the farmer and to overcome the problem of overproduction which can make onions cheaper and can also cause the onions to rot, this will cause losses to the farmers. To overcome this, product diversification needs to be implemented, one of which is to make fresh shallots into fried onions.